Improving Latex‐Based Pressure‐Sensitive Adhesive Properties Using Carboxylated Cellulose Nanocrystals. Issue 3 (5th January 2022) - Gabriel, Vida A.; Tousignant, Mathieu N.; Wilson, Sean M.W.; Faure, Marie D.M.; Cranston, Emily D.; Cunningham, Michael F.; Lessard, Benoît H.; Dubé, Marc A.
Abstract: Cellulose nanocrystals (CNCs) are becoming a popular option when producing polymer nanocomposites because they are a green alternative to petroleum‐based performance enhancers and provide significant matrix reinforcement at low loadings. DextraCel is a commercial grade CNC with carboxylate surface groups that can be dispersed in water without sonication. These carboxylated CNCs (cCNCs) can be incorporated in situ via seeded semi‐batch emulsion polymerization to produce latexes for adhesive applications. The resulting nanocomposite films exhibit 26 x higher peel strength, 4.5 x higher tack, and 7.7 x higher shear strength relative to base case films. Curiously, adhesives produced from latexes containing cCNCs that do not undergo ultrasonication display greater adhesive property improvements relative to films produced with cCNCs that are ultrasonicated. Atomic force microscopy images reveal that cCNCs have stronger self interactions than their sulfated CNCs counterparts; cCNCs display side‐by‐side and end‐to‐end association in films when they are not ultrasonicated, which increases their "apparent" aspect ratio—an important characteristic attributed to matrix reinforcement. Omitting ultrasonication preserves cCNC‐cCNC interactions that cause them to behave like nanofibers rather than discrete nanocrystals; this allows them to display greater mechanical enhancements, similar to reinforcements provided by nanofibrils, without the technical challenges associated with producing composite latexes with nanofibrils. Abstract : Cellulose nanocrystals are being increasingly used as sustainable polymer property modifiers. Carboxylated cellulose nanocrystals (cCNCs) are used in this study to improve the adhesive qualities of films cast from latexes and indeed, resulting nanocomposite adhesives are significantly stronger than films without cCNCs.